2016
DOI: 10.1088/0031-9155/61/13/4763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of transcytolemmal water exchange analysis for therapeutic response assessment using DCE-MRI: a comparison study

Abstract: This study compares the Shutter-Speed (SS) and the Tofts models as used in assessing therapeutic response in a longitudinal DCE-MRI experiment. Sixteen nu/nu mice with implanted colorectal adenocarcinoma cell line (LS-174T) were randomly assigned into treatment/control groups (n=8/group) and received bevacizumab/saline twice weekly (Day1/Day4/Day8). All mice were scanned at one pre- (Day0) and two post-treatment (Day2/Day9) time points using a high spatiotemporal resolution DCE-MRI pulse sequence. The CA extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The elegant two‐compartment model design assumes infinite transcytolemmal water exchange, which may not be true, particularly with high CA concentration 233 . Comparison studies showed that K trans derived with and without infinite transcytolemmal water exchange assumptions had different performances in capturing anti‐vascular treatment effect 234 . Understanding the limitations of physiological assumptions is also critical in optimizing a data analysis method.…”
Section: Challenges and Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elegant two‐compartment model design assumes infinite transcytolemmal water exchange, which may not be true, particularly with high CA concentration 233 . Comparison studies showed that K trans derived with and without infinite transcytolemmal water exchange assumptions had different performances in capturing anti‐vascular treatment effect 234 . Understanding the limitations of physiological assumptions is also critical in optimizing a data analysis method.…”
Section: Challenges and Limitsmentioning
confidence: 99%
“…233 Comparison studies showed that K trans derived with and without infinite transcytolemmal water exchange assumptions had different performances in capturing anti-vascular treatment effect. 234 Understanding the limitations of physiological assumptions is also critical in optimizing a data analysis method. Similarly, in a DWI study using different b values, when high b values were used as acquisition parameters for imaging, results indicated extra pathology results and suggested different modeling for more adequate interpretation.…”
Section: Clinical Interpretationsmentioning
confidence: 99%